Express analysis of water reservoirs with the components of rocket fuel - Pushkin, Игорь Александрович; Kozlovskaya, Элла Борисовна; Zaloznaya, Наталия Геннадьевна (Chrezvychaynye situatsii: obrazovanie i nauka, 2007)
The express method of defining the concentration of non-symmetric dimethylhydrazine in open water reservoirs with the help of chemoluminescent method is considered in the article.